DAMPAK PEMBANGUNAN BANDARA KUALANAMU TERHADAP NILAI TANAH (Studi Pada Kantor Kecamatan Beringin, Kabupaten Deli Serdang) - Sharfina, Sarayati (Universitas Medan Area, 2015)
Development can be defined as `a coordinated effort to create an alternative that is more rightfully given to every citizen to me?menuhi and achieve the aspirations of the most humane. Development is a change from something insignificant to something more meaningful This research was conducted at the Head Office Beringin Deli Serdang, this study included descriptive study with qualitative approach, method of data collection is done by in-depth interviews with informants predetermined or by observation.This study aimed to explore the real impact of the construction of Kuala Namu Airport. The results of interviews with informants indicates the fact that the construction of Kuala Namu Airport have a significant effect on the increase in the value of land in the area surrounding Kuala Namu Airport.